Application of systems thinking in teaching life sciences : effects on students' conceptual understanding and attitudes - DELA CRUZ, REGINA T. (Archīum Ateneo, 2019)
This study explored the use of Systems Thinking in Biology instruction and its effects on students conceptual understanding and learning attitudes. Two statistically-equivalent (in terms of Science achievement) groups, the Conventional Learning (CL) and Systems Thinking (ST) groups, were taught the same learning competencies, but with the use of traditional learning strategies for CL and Systems Thinking tools (causal-loop diagrams and behavior-over-time graphs) for ST. Both groups improved their conceptual understanding based on paired samples t test analysis of pretest and posttest scores, but the ST group performed better and developed more positive attitudes as indicated by the independent samples t test of the scores in the posttest and post-attitudinal survey. The ST group also achieved significantly higher normalized gain scores in the conceptual questions that required higher-order thinking skills. Supported by qualitative data from focus group discussions, the results of this study present the potential of Systems Thinking in helping the students realize conceptual connections, improve understanding of the topics and higher-order thinking skills, and develop more positive learning attitudes.